Exante economic impact assessment of genetically modified banana resistant to Xanthomonas wilt in the great lakes region of Africa - Ainembabazi, John H.; Tripathi, L.; Rusike, Joseph; Abdoulaye, Tahirou; Manyong, Victor M. (Public Library of Science, 2015)
Credible empirical evidence is scanty on the social implications of genetically modified (GM) crops in Africa, especially on vegetatively propagated crops. Little is known about the future success of introducing GM technologies into staple crops such as bananas, which are widely produced and consumed in the Great Lakes Region of Africa (GLA). GM banana has a potential to control the destructive banana Xanthomonas wilt disease.